210k views
0 votes
Factor this polynomial completely. If it will not factor state that in the answer.

Factor this polynomial completely. If it will not factor state that in the answer-example-1

1 Answer

3 votes

The given expression is,


x^2-x-42

We have,


\begin{gathered} -7x+6x=-x \\ -7*6=42 \end{gathered}

We can rearrange the above expression as,


\begin{gathered} x^2-x-42=x^2-7x+6x-42 \\ \text{ =x(x-7)}+6(x-7) \\ \text{ =(x-7)(x+6)} \end{gathered}

User Juan Carlos Moreno
by
4.8k points